Concept and Indications of Secular State - N. V. Philina (Сибирское юридическое обозрение, 2014)
The article deals with the elaborate analysis of the concept and indications of a secular state. The paper has the interdisciplinary character and it is written on the verge of constitutional law, theory of state administration, philosophy, political science. The comparative analysis between the constitutional indicators of a secular state and democracy realia has been conducted.